A mechanistic analysis of shell-side two-phase ﬂow in an idealised in-line tube bundle - McNeil, David A.; Sadikin, Azmahani; Bamardouf, Khalid H. (Elsevier Ltd, 2012)
This paper reports on an experimental study of air–water mixtures ﬂowing through an idealised shell and tube, in-line heat exchanger. Void fraction measurements are reported for the minimum gaps between the tubes at near atmospheric conditions. The pressure distributions around some tubes are also reported. These data are combined with data available in the open literature to investigate pressure drop and void fraction prediction methods for these heat exchangers. The data are shown to be ﬂow pattern dependent. Criteria for ﬂow pattern boundaries are deduced from previously published ﬂow maps. Void fraction data in the maximum gap between the tubes are shown to be compatible with the drift ﬂux model and to be different in magnitude to the minimum gap values, which are shown to result from acceleration phenomena in the gaps between the tubes. The pressure drop data are analysed through a one-dimensional model that incorporates separation and re-attachment phenomena. The frictional pres-sure drop is shown to depend on a liquid layer located on the upper portion of the tubes at low gas veloc-ity and on acceleration effects at high gas velocity.